Scalable and continuous production of dehydrated protein microparticles as an alternative to lyophilisation - Booth, Thomas (2023)
The work described within this thesis had the primary aim to investigate a protein dehydration technique named Critical Concentration Precipitation (CCP) and to assess the potential of this technique for industrial use an alternative to lyophilisation. The physical mechanism underlying this technique was studied using a dual micropipette method capable of generating individual aqueous droplets within a solvent reservoir. It was demonstrated that protein concentration within the droplet can be calculated at any time point within the experiment and that through further experimentation the particle size and process time could be modelled as a function of initial droplet size and concentration. Bulk CCP microparticle samples were later prepared, rehydrated and analysed spectroscopically to assess any degradation to the protein molecules caused by the CCP process. Analysis of protein structure and aggregation showed that the CCP process and subsequent reconstitution did not induce significant structural changes or increase aggregation of the protein. Scale up of the process was then demonstrated using laboratory-scale representations of industrial processes. To further assess the applicability of the CCP process for use as an alternative to lyophilisation, a year-long stability study was conducted. Bovine serum albumin (BSA) and human serum albumin (HSA) formulations were dehydrated and stored at 5°C, 25°C and 40°C for up to one year with characterisation carried out at defined timepoints throughout the study. Spectroscopic analysis of the samples throughout the year demonstrated that all protein formulations tested, across all temperatures, experienced no significant disruptions to their tertiary structure. Aggregation measurements showed that the CCP formulations experienced greater overall increases in aggregation than their lyophilised counterparts. However, it was also shown that the lyophilised samples experienced a greater increase in larger, non-soluble aggregates. Continuous fluidic devices were tested to demonstrate the feasibility of continuous CCP manufacture, with the T-reactor method showing control of aqueous droplet size through manipulation of flow rates. However, this size control did not translate to the resultant microparticles with all samples measuring similar size profiles. This was shown to be due to a homogenisation effect from the stirred reservoir used to suspend the droplets. Replacing the stirred reservoir with an unstirred design resulted in the production of highly uniform microparticles of a different size, implying that the new process did not have the same homogenising effect. For CCP technology to be accepted as an industrial technique it must be capable of solidifying more proteins than just albumins. Through two screening studies it was shown that a potentially wide range of solvents can be used as the drying solvent and that multiple proteins could be dehydrated and rehydrated without causing degradation to the protein structure. Interestingly, the use of methyl acetate as the drying solvent resulted in large flakes of protein material that started to solidify as soon as the aqueous phase was added to the reservoir, before droplet dispersion via vortex mixing. Furthermore, it was shown that any salts present within the aqueous protein solution were also dehydrated to form crystalline structures, implying that other molecules may also be dehydrated using this technique. The final work discussed in this thesis is preliminary data showing the potential for CCP microparticle formulations to be used in high concentration, non-aqueous suspensions for injectables and as a dissolution aid and transport scaffold for low solubility drugs. These proof-of-concept studies showed that high concentration protein suspensions in benzyl benzoate measured lower viscosity than an equivalent concentration aqueous solution and that the low solubility drug, indomethacin appeared to have been incorporated into a BSA microparticle formulation with an encapsulation efficiency of 33%.